ANALISIS EFISIENSI TEKNIS DAN SKALA EKONOMI INDUSTRI PERBANKAN SYARIAH DI INDONESIA - Amalo, Fitriningsih (Manajemen Bisnis, 2012)
Fitriningsih AmaloUniversitas Muhammadiyah KupangE-mail: ithyamalo@yahoo.comABSTRACTThis study aimed to measure the extent of technical efficiency of Islamic banking industry, analyzingpotential improvements composition of input and output, determine the source of technical efficiency,and to know the position of economies of scale. The analysis technique used Data EnvelopmentAnalysis (DEA). The determination of input and output used the intermediation approach. The variablesinputs are namely deposits, fixed assets, labour costs, and outputs (financing). Sampling techniqueis purposive sampling. Sample size are 18 banks the period 2007-2010. The results showedthat the technical efficiency of Islamic banking industry experienced volatile growth, the averagetechnical was not efficient (inefficiency). The efficient scored are namely DKI Bank (2007), Bank ofEast Java (2007), Bank of West Kalimantan (2007), Permata Bank (2008-2009), and Bank of westJava (2010). The sources of technical inefficiency in the Indonesian Islamic banking industry wasfrom the input and output variables. The potential improvements should be done by the bank tooptimize the use of inefficient input for maximizing output. Technical efficiency value was dominatedby pure technical efficiency while low scale efficiency and economies of scale position of Islamicbanking industry in Indonesia. During the period of observation shows the constant Condition Returnto Scale (CRS) four banks, Decreasing Return to Scale (DRS).The condition of the banks IncreasingReturn to Scale (IRS) were 13 banks. This condition means that the increase in output will befollowed by lower costs.Keywords: Technical Efficiency, Economies of Scale, Islamic Banking Industry, Data EnvelopmentAnalysis.